ANALISIS PENILAIAN PERILAKU KOMUNIKASI PESERTA DIDIK SEKOLAH MENENGAH PADA PELAKSANAAN UJIAN NASIONAL (Studi Kasus pada Sistem Manual-2014 dan Online-2015 di SMPK 2 Penabur Jakarta) - RUSTONO FARADY MARTA; HARRIS CHRISTANTO (Jurusan Ilmu Komunikasi UTM, 2016)
ABSTRACTIn 2015, Ministry of Education and Culture, Republic of Indonesia did abreakthrough in the educational communication field, it is online-nationalexamination, known as computer based test. In Jakarta, implementation ofcomputer based test is coordinated by Provincial Education Board of DKIJakarta and caried out 30 schools which consist of 1 junior high school, 3senior high schools, and 26 vocational schools. SMPK 2 Penabur Jakarta wasthe first and chosen by government to run that new examination method. Thepurpose of this research is to know about comparison between paper basedtest in 2014 and computer based test in 2015 at SMPK 2 Penabur Jakarta,that was held on May 4 until 7, 2015. Selection of research subject was basedon psychological characteristic of 9 grade students in junior high school(14 – 15 years old) who prioritized to observe on. The research applied socialjudgment theory by Muzafer Sherif. This qualitative-descriptive research usedcase study method and based on constructivism paradigm. Data collection wasconducted by interview, Focus Group Discussion (FGD), and documentationstudy through online media. The result of this study shows that computer basedtest is more excellent than paper based test. SMPK 2 Penabur Jakarta gavepositive response for this innovation.Keywords: Educational Communication, National Examination, SocialJudgment, Junior High School Students.Judgment, Junior High School Students.